Effects of Hepatocyte CD14 Upregulation during Cholestasis on Endotoxin Sensitivity - Chou, Ming-Huei; Chuang, Jiin-Haur; Eng, Hock-Liew; Tsai, Po-Chin; Hsieh, Chih-Sung; Liu, Hsiang-Chun; Wang, Chiou-Huey; Lin, Chih-Yun; Lin, Tsun-Mei (PLOS ONE, 2012)
Cholestasis is frequently related to endotoxemia and inflammatory response. Our previous investigation revealed a significant increase in plasma endotoxin and CD14 levels during biliary atresia. We therefore propose that lipopolysacharides (LPS) may stimulate CD14 production in liver cells and promote the removal of endotoxins. The aims of this study are to test the hypothesis that CD14 is upregulated by LPS and investigate the pathophysiological role of CD14 production during cholestasis. Using Western blotting, qRT-PCR, and promoter activity assay, we demonstrated that LPS was associated with a significant increase in CD14 and MD2 protein and mRNA expression and CD14 promoter activity in C9 rat hepatocytes but not in the HSC-T6 hepatic stellate cell line in vitro. To correlate CD14 expression and endotoxin sensitivity, in vivo biliary LPS administration was performed on rats two weeks after they were subjected to bile duct ligation (BDL) or a sham operation. CD14 expression and endotoxin levels were found to significantly increase after LPS administration in BDL rats. These returned to basal levels after 24 h. In contrast, although endotoxin levels were increased in sham-operated rats given LPS, no increase in CD14 expression was observed. However, mortality within 24 h was more frequent in the BDL animals than in the sham-operated group. In conclusion, cholestasis and LPS stimulation were here found to upregulate hepatic CD14 expression, which may have led to increased endotoxin sensitivity and host proinflammatory reactions, causing organ failure and death in BDL rats.